A Method to Provide Accessibility for Visual Components to Vision Impaired - Nazemi, Azadeh; Murray, Iain (CSC Journals, 2013)
Non-textual graphical information (line graphs, bar charts, pie charts, etc.) are increasingly pervasive in digital scientific literatures and business reports which enabling readers to easily acquire the nature of the underlying information [1]. These graphical components are commonly used to present data in an easy-to interpret way. Graphs are frequently used in economics, mathematics and other scientific subjects. In general term data visualization techniques are useless for blind people. Being unable to access graphical information easily is a major obstacle to blind people in pursuing a scientific study and careers [2].This paper suggests a method to extract implicit information of Bar chart, Pie chart, Line chart and math’s graph components of an electronic document and present them to vision impaired users in audio format. The goal is to provide simple to use, efficient, and available presentation schemes for non textual which can help vision impaired users in comprehending form without needing any further devices or equipment. A software application has been developed based on this research. The output of application is a textual summary of the graphic including the core content of the hypothesized intended message of the graphic designer. The textual summary of the graphic is then conveyed to the user by Text to Speech software.The benefit of this approach is automatic providing the user with the message and knowledge that one would gain from viewing the chart.